Aplicación del ciclo de vida BPM en el proceso de postcosecha en una empresa del sector floricultor. (2019)
In the constant growth of the floricultural industry in Colombia, the continuous improvement of processes requires the implementation of new models and technologies that allow to maintain in this market in an efficient and sustainable way Due to, the Business Process Management BPM, has proven to be appropriate for Increase performance and competitiveness in the main processes of an organization. The life cycle was applied to the post-harvest process, considering that the scope of this study reaches the proposal of redesign and improvement proposals, showing that this study is valuable, since in general the flower growing companies have the same problems and disadvantages. Therefore, this article presents improvements that can be used by companies in this sector.